Produção e qualidade da batata doce em respostas a doses de nitrogênio e potássio e lâminas de irrigação - Sarmento, Diogenes Henrique Abrantes (Universidade Federal Rural do Semi-Árido, 2019)
Sweet potatoes have been highlighted as healthy food, being indicated in low-calorie diets in unrestricted human food. It is cultivated in all Brazilian regions, with greater presence in the Northeast and Southeast regions. Nitrogen and potassium are the two most important macronutrients, whose function is to store energy in photosynthesis and respiration, as well as energy for protein synthesis reactions, biological nitrogen fixation. Due to the water restriction for use in the irrigated perimeters and the demand for new crops that require smaller irrigation slides and have compatible marketing values, the behavior of the sweet potato crop was studied in a Quartzarenic Neosol submitted to different irrigation slides determined (L1: 452 mm (60% of ETc), L2: 568 mm (80% of ETc), L3: 684 mm (100% ETc) and L4: 801 mm 138 days after planting, of which 104 mm for all treatments in the first 15 days and between 121 and 165 days, it rained 392 mm. The N or K doses in each trial were randomized blocks with four replicates and Nitrogen (N) (N1: 10, N2: 40, N3: 75, N4: 110 and N5: 150 kg ha-1) or potassium doses (K1; 0; K2: 50; K3: 100; K4: 150 and K5: 200 kg ha-1 K2O). The nutrients were applied in fertigation. The source of N was calcium nitrate and K was potassium chloride, applied from the twentieth day after planting (DAP) for all treatments, as a source of phosphorus applied the MAP. The applied water slides were 452, 568, 684 and 801 mm ha-1 until 138 days after. The variables analyzed were: total and commercial productivity, number of tubers, average tuber mass, and quality (Firmness, Soluble Solids and Starch). It is recommended the application of the L1 blade, 60% of ETc estimated for the sweet potato crop, and 40 kg ha-1 Nitrogen dose. The quality of the potato was not altered with the doses of N and irrigation slides. The starch content was increased in response to the dose of N depending on the applied irrigation Blade. There was a positive response of production to increase of dose of K
Keywords: Ipomoea batatas; Fertirrigação; Manejo de irrigação; Adubação nitrogenada; Potássica; Ipomoea potatoes; Fertirrigation; Irrigation management; Nitrogen fertilization; Potassium; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO